Salivary microbiota reflecting changes in subgingival microbiota - Jae-Suk Jung; Joong-Ki Kook; Soon-Nang Park; Yun Kyong Lim; Geum Hee Choi; Sunjin Kim; Suk Ji (Microbiology Spectrum)
ABSTRACT The purpose of this study was to determine whether subgingival microbial changes according to the severity of periodontal disease and following the non-surgical periodontal treatment of periodontitis are reflected in the saliva microbiota. Subgingival and saliva samples were collected from 7 periodontally healthy controls, 14 patients with gingivitis, 12 with moderate periodontitis, and 18 with severe periodontitis. Among subjects who received treatment, seven moderate and seven severe periodontitis patients were selected for post-treatment microbial analysis, and their samples were analyzed at baseline and 6 months after treatment. The V3 and V4 regions of the 16S rRNA gene were sequenced, and correlations of the relative abundance of phyla and health- or periodontitis-dominant species between subgingival plaque and saliva samples were analyzed using Spearman signed-rank tests. Alpha diversity was higher in saliva than subgingival plaque samples, and beta diversity was significantly different between the two samples. However, levels of phyla and most health- or periodontitis-dominant species in salivary microbiota were significantly correlated with those in subgingival plaque. The improvement in clinical parameters following treatment was accompanied by a microbial shift not only in subgingival plaque but also in saliva. The abundance of 2 phyla including Bacteroidetes, 6 genera including Porphyromonas and Treponema, and 11 species including Porphyromonas gingivalis, Tannerella forsythia, and Filifactor alocis was significantly reduced in saliva following treatment. These results indicate that the salivary microbiota can reflect changes in the subgingival microbiota, suggesting that saliva can be used as a diagnostic tool to monitor the periodontal health status of individuals.IMPORTANCEThe salivary microbiota has attracted increasing attention as a promising method for monitoring periodontal disease. With regard to the pathogenesis of periodontal disease, however, subgingival plaque microbiota is the dominant etiological factor. Although it has been established that periodontopathogenic bacteria exist in saliva and their distribution differs, depending on the severity of the disease, it is necessary to analyze the extent to which the salivary microbiota reflects the subgingival microbiota. This study explored whether subgingival microbial changes according to the severity of periodontal disease and following the non-surgical periodontal treatment of periodontitis are reflected in the saliva microbiota and concluded that the salivary microbiota can reflect changes in the subgingival microbiota. Saliva can be used as a diagnostic tool to monitor the periodontal health status of individuals.